Digital trade integration in preferential trade agreements - Andrew D. Mitchell; Neha Mishra (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2020)
The growth of digital trade is dependant upon greater interconnectivity across borders. Several countries strive to achieve such interconnectivity and integration in digital trade through international trade agreements. Digital trade integration is a complex, multidimensional process that integrates regulatory structures/policy designs, digital technologies and business processes along the entire global/regional digital value chain. This paper sets out five foundational elements of digital trade integration: reducing digital trade barriers; digital trade facilitation; digital trade regulatory frameworks and digital trust policies; digital development and inclusion; and institutional coordination. It then examines the extent to which Preferential Trade Agreements (PTAs) can or do contribute to digital integration. Some recent PTAs contain ambitious provisions to reduce regulatory barriers in digital trade and facilitate cross-border data flows. However, most PTAs fail to holistically support the five pillars of digital trade integration, and are particularly deficient in supporting digital development and inclusion, incorporating adequate digital trade facilitation measures, and facilitating meaningful international regulatory cooperation. This paper provides various policy recommendations to address such deficiencies. This paper also contains a case study of digital trade integration in the Association of Southeast Asian Nations (ASEAN). It argues that the ASEAN framework currently functions as a weak form of digital trade integration, focusing mainly on political goodwill and high-level cooperation. Although the ASEAN Members are committed to enhancing regulatory cooperation and strengthening their institutions on electronic commerce, the development asymmetry coupled with the conflicting policy preferences of ASEAN Members remains a key obstacle.
Keywords: F10; F13; 330; Digital trade; Digital trade integration; Trade barriers; International trade; PTAs; Trade facilitation; Trade policy; ASEAN